2019
DOI: 10.1063/1.5079516
|View full text |Cite
|
Sign up to set email alerts
|

Vortex shedding suppression in mixed convective flow past a square cylinder subjected to large-scale heating using a non-Boussinesq model

Abstract: In the present work, numerical simulations are performed to investigate the vortex shedding suppression phenomenon for mixed convective flows past a square cylinder in the large-scale heating regime. A full compressible flow model with variable transport and thermo-physical properties is employed to capture large-scale heating effects. The Reynolds number, Prandtl number, and Mach number are kept constant at Re = 100, Pr = 0.71, and M = 0.1, while the cylinder inclination (ϕ), free-stream inclination (α), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Wakes behind other bluff bodies such as square 12,13 and elliptic cylinders have been investigated due to the practical impact on submarines 14 and heat exchangers. 15 For elliptic cylinders, the flow depends on both the aspect ratio (AR) of the elliptic cylinder (defined by the ratio of the semi-minor to semi-major axis length) and the incident angle (defined by the angle between the inlet flow direction and the semi-minor axis) in addition to the Reynolds number based on the free-stream velocity and the semi-major axis length.…”
Section: Introductionmentioning
confidence: 99%
“…Wakes behind other bluff bodies such as square 12,13 and elliptic cylinders have been investigated due to the practical impact on submarines 14 and heat exchangers. 15 For elliptic cylinders, the flow depends on both the aspect ratio (AR) of the elliptic cylinder (defined by the ratio of the semi-minor to semi-major axis length) and the incident angle (defined by the angle between the inlet flow direction and the semi-minor axis) in addition to the Reynolds number based on the free-stream velocity and the semi-major axis length.…”
Section: Introductionmentioning
confidence: 99%
“…Since three-dimensional flow around the human head is similar to the flow around the bluff bodies, it is important to consider the previous investigations who considered heat transfer and fluid flow past the bluff bodies or vortex generators [5,[7][8][9][10][11][12]. For example, Arif and Hasan [7] studied the flow around a square cylinder and analyzed the vortex shedding phenomena considering effective parameters. Bayareh et al [12] investigated the effect of vortex generator on heat transfer of a flat plate and demonstrated that as the angle of vortex generator increases, the longitudinal vortices become stronger.…”
Section: Introductionmentioning
confidence: 99%